Volatile Flavor Compounds Profile and Fermentation Characteristics of Milk Fermented by Lactobacillus delbrueckii subsp. bulgaricus - Dan, Tong; Ren, Weiyi; Liu, Yang; Tian, Jiale; Chen, Haiyan; Li, Ting; Liu, Wenjun (Frontiers in Microbiology, 2019)
Lactobacillus delbrueckii subsp. bulgaricus is one of the predominant lactic acid bacterial species used as starter cultures in industrial fermented dairy manufacturing, as it strongly affects the quality of the products. Volatile flavor compound profiles and fermentation characteristics are considered the most important indicators for starter culture screening. In the present study, volatile compounds in milk fermented by 17 test strains of L. delbrueckii subsp. bulgaricus and a commercial strain used as a control were identified using solid-phase microextraction (SPME) methods coupled with gas chromatography mass spectrometry (GC-MS). In total, 86 volatile flavor compounds were identified in the fermented milk upon completion of fermentation, including 17 carboxylic acids, 14 aldehydes, 13 ketones, 29 alcohols, 8 esters, and 5 aromatic hydrocarbon compounds. Various volatile flavor compounds (acetaldehyde, 3-methyl-butanal, (E)-2-pentenal, hexanal, (E)-2-octenal, nonanal, 2,3-butanedione, acetoin, 2-heptanone, 2-nonanone, formic acid ethenyl ester) were identified due to their higher odor activity values (> 1). In addition, of the 17 test strains of L. delbrueckii subsp. bulgaricus, IMAU20312 (B14) and IMAU62081 (B16) strains exhibited good fermentation characteristics in milk compared with the control strain. The combination of the volatile flavor compound profile and fermentation characteristics in this work could be useful when selecting lactic acid bacteria that may serve as important resources in the development of novel fermented milk products.